Design, Synthesis and Biological Evaluation of Nucleozin Sulfonyl Piperazine Derivatives as Anti-influenza A Virus Inhibitors - Pei, Shuchen; Chen, Junlin; Yang, Jinhua; Lai, Lin; Huang, Xiang; Xu, Mingxin; Chen, Jun (Letters in Organic Chemistry, 2023)
Influenza A viruses have caused worldwide epidemics and pandemics by reassortment and generation of drug-resistant mutants, which leads to an urgent need to develop novel antivirals. In this study, a series of sulfonyl piperazine nucleozin derivatives were designed and synthesized, and their in vitro anti-influenza activity was evaluated. Many of these compounds exhibited moderate to good anti-influenza activity against influenza A. Among these, 6d, 6g, 6h, 6i, and 6j exhibited better activity than ribavirin. 2,3-dichlorobenzene substituted analogue 6i displayed the most remarkable in vitro activity against Influenza A. All the derivatives show no obvious cellular growth inhibition against MDCK cells. This study reported a new series of nucleoprotein inhibitors with a good selectivity window and potential for further development as novel anti-influenza agents.
Keywords: synthesis